Rehabilitación kinésica como tratamiento para la enfermedad de dupuytren en adultos jóvenes - Jefferson Xavier, Aspiazu Espin (2021)
ABSTRACT The research elaborated under the modality of bibliographic review, so its main objective was to know and expose the benefits of kinesiotherapy in patients with Dupuytren's disease. Kinesiotherapy is essential in different osteoarticular pathologies, especially Dupuytren's disease, since it allows us to successfully complete the rehabilitation that is carried out. However, kinesiotherapy is not applied in our environment, despite this there is a great variety of information, so 120 scientific articles could be found, of which several of them discarded, by means of exclusion criteria and score through the PEDro scale, then we worked with 35 scientific articles which reached a score equal or higher than 7 in order to enrich the research, these articles digitized in different languages such as: Portuguese, English and Spanish, allowing to collect more information about the topic raised. For the collection of scientific articles, different databases used, such as NCBI, PudMed, Scielo, Elservier, among others. These scientific articles collected from 2005 to 2020. Finally, after the discussion, considering the information presented by the different authors, it concluded that kinesiotherapy does represent great benefits for Dupuytren's disease. Key words: kinesiotherapy, Dupuytren's disease, kinesic rehabilitation. Firmado electrónicamente por: MARITZA DE LOURDES CHAVEZ AGUAGALLO Reviewed by: Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324